Közös vagy kizárólagos szülői felügyelet? : A gyermek érdekének érvényre jutására a polgári kortól napjainkig - Visontai-Szabó, Katalin (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2023)
Nowadays, as long as parents live together, it is usually not disputed that they jointly exercise their parental rights over their child. It was not so clear before. Before the Family Law Act entered into force in 1953, fathers had additional rights compared to mothers, as long as they raised the child in a joint household. After the breakup of the relationship, strict rules determined which parent was entitled to exercise parental custody rights. When making its decision, the court placed particular emphasis on the sex and age of the child, as well as which parent’s fault led to divorce. In the second half of the 20th century, the rights of parents were equalized, but after the end of marriage, it became natural for a long time, that mothers should raise their children alone. Following the amendment of the Civil Code the joint responsibility of the parents in raising the child is now of paramount importance, and the enforcement of the child's interests is becoming more and more important.